The Implementation Of Corporate Social Responsibility (Csr) Communication In The Company Pt. Hindoli - Dimas Desrianto; Ahmad Muhaimin; Putri Citra Hati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research has the main objective of identifying and analyzing the implementation of CSR communication in PT. Hindoli. The problems contained in this study are the inconsistency between the programs run by the company and the expectations of the community, the lack of transparency in the delivery of information, and the lack of feedback mechanisms from the communities involved. The type of research used is field research with a qualitative approach that is descriptive. The data collection methodology used in this study is observation, documentation and interviews. The primary data sources in this study are HR Management, CSR Staff and Beneficiary Communities. The technique for analyzing data is through three stages, namely: 1) data reduction, 2) data presentation, and 3) drawing conclusions or verification. Based on the results of the research on the implementation of the CSR program of PT. Hindoli has run quite well through the two-way communication pattern between the company and the community and the accuracy of the implementation of communication of CSR recipients at PT. Hindoli can be said to be quite effective because it is carried out through participatory communication involving village officials, community leaders, and the surrounding community.